2018
DOI: 10.1002/pmic.201700253
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Native and Posttranslationally Modified HLA‐B*57:01‐Restricted HIV Envelope Derived Epitopes Using Immunoproteomics

Abstract: The recognition of pathogen-derived peptides by T lymphocytes is the cornerstone of adaptive immunity, whereby intracellular antigens are degraded in the cytosol and short peptides assemble with class I human leukocyte antigen (HLA) molecules in the ER. These peptide-HLA complexes egress to the cell surface and are scrutinized by cytotoxic CD8+ T-cells leading to the eradication of the infected cell. Here, naturally presented HLA-B*57:01 bound peptides derived from the envelope protein of the human immunodefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…Cell culture and isolation of p-HLA complexes Monoallelic cell lines were generated from C1R cells transfected with HLA alleles of interest and include C1R-A*01:01, C1R-B*07:02, C1R-B*08:01, C1R-B*15:02, C1R-B*18:01, C1R-B*27:05, C1R-B*57:01, C1R-B*57:03, and C1R-B*58:01 (24,(31)(32)(33). These cells were grown to high density in RPMI 1640 media supplemented with 10% fetal calf serum, 7.5 mM Hepes, streptomycin (150 mg/ml), benzylpenicillin (150 U/ml), 2 mM L-glutamine (MP Biomedicals), 76 mM b-mercaptoethylamine, and 150 mM nonessential amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture and isolation of p-HLA complexes Monoallelic cell lines were generated from C1R cells transfected with HLA alleles of interest and include C1R-A*01:01, C1R-B*07:02, C1R-B*08:01, C1R-B*15:02, C1R-B*18:01, C1R-B*27:05, C1R-B*57:01, C1R-B*57:03, and C1R-B*58:01 (24,(31)(32)(33). These cells were grown to high density in RPMI 1640 media supplemented with 10% fetal calf serum, 7.5 mM Hepes, streptomycin (150 mg/ml), benzylpenicillin (150 U/ml), 2 mM L-glutamine (MP Biomedicals), 76 mM b-mercaptoethylamine, and 150 mM nonessential amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…Such knowledge can then be used to inform the antigenic composition of T cell-based vaccines, so they can be formulated as individual peptides, long epitope-rich peptides, mosaic peptides or even whole protein antigens to focus the immune response towards conserved and protective epitopes. Here, we defined the CD8 + T cell cross-reactome against influenza A, B and C viruses and identified the antigenic specificity of IBV CD8 + T cells using immunopeptidomics 20,21 . We demonstrated that CD8 + T cells can confer a previously unrecognized, broadly heterotypic cross-reactivity and characterized these responses in depth.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, through a series of convincing experiments, the authors demonstrate that IDO1 is able to convert W residues also within polypeptides peptides, and that the presence of kynurenine is not an artifact due to sample handling or the purification process. Another modified HIVenv peptide with a deamidation on the asparagine (N) was identified in the same study . Notably, the peptide most likely originally harbored an N‐glycan which could have been processed by the cytosolic peptide N‐glycanase .…”
mentioning
confidence: 82%
“…In particular, some HLA class I allotypes, such as HLA‐B*57:01, seem to have “protective” properties on disease progression . In this study, Ramarathinam et al . transfected the C1R cell line with the HIV envelope (HIVenv) protein in order to assess the presentation of the viral antigens on the HLA‐B*57:01 allele.…”
mentioning
confidence: 99%